2017
DOI: 10.3892/mmr.2017.8074
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of atorvastatin on cerebral vessel autoregulation in an experimental rabbit model of subarachnoid hemorrhage

Abstract: The aim of the present study was to assess the therapeutic effects of atorvastatin on cerebral vessel autoregulation and to explore the underlying mechanisms in a rabbit model of subarachnoid hemorrhage (SAH). A total of 48 healthy male New Zealand rabbits (weight, 2–2.5 kg) were randomly allocated into SAH, Sham or SAH + atorvastatin groups (n=16/group). The Sham group received 20 mg/kg/d saline solution, whereas 20 mg/kg/d atorvastatin was administered to rabbits in the SAH + atorvastatin group following SAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Each process consumes energy and is regulated by cell signaling pathways, which is the basis for this type of death being called programmed cell death. However, none of these mechanisms fully explain the early brain damage caused by acute CNS disease (Chen et al, 2016(Chen et al, , 2018Zille et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Each process consumes energy and is regulated by cell signaling pathways, which is the basis for this type of death being called programmed cell death. However, none of these mechanisms fully explain the early brain damage caused by acute CNS disease (Chen et al, 2016(Chen et al, , 2018Zille et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Statins can reduce the concentration of glutamate by upregulation of nitric oxide synthase, and Jiang [28] also found that statins can inhibit 5-HT and 5-HTT expression in chronic obstructive pulmonary disease and pulmonary artery hypertension, then it may be ameliorated delirium by regulating neurotransmitters. Many previous studies indicated that statins can alleviate cerebral vasospasm, cerebral perfusion, prevents endothelial dysfunction, and ameliorating neuronal apoptosis and brain injury [7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Statins, as inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, are widely used in cardiovascular disorders as cholesterol-lowering medications. Recent studies had indicated that statins have been proven to exert pleiotropic effects, including anti-inflammatory, antioxidative stress, inhibit platelet aggregation, and neuroprotection [7][8][9][10]. As the neuroprotection related molecular mechanism was similar to the delirium, so it indicated that statins may prevent delirium.…”
Section: Introductionmentioning
confidence: 99%
“…After conservative treatment fails to control refractory intracranial hypertension (e.g., ICP >25 mmHg for a long period of time), there is sufficient evidence to support the use of decompression as a life-saving intervention [17]. Rapid decompressive craniectomy can reduce ICP, thus improving cerebrovascular compliance [18], cerebral oxygenation [19,20], and cerebral perfusion [21,22], and can also reduce postoperative brain edema [11], but it also leads to a high probability of rebleeding and brain swelling during surgery or post-operatively. Flint et al reported that 58% of patients (n=40) experienced acute encephalocele and ipsilateral or contralateral rebleeding with rapid decompressive craniectomy [23], which sharply increases ICP and aggravates cytotoxicity and angiogenic brain edema [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral scores were recorded by an evaluator who did not participate in the experiment. A scoring table was used to assess neural function at 24 h after the operation [10,11]. The behavioral study included the following 3 tests: I) Appetite.…”
Section: Methodsmentioning
confidence: 99%